THE IDIOMATIC MEANING OF æˆè¯ CHENGYU WHICH HAS NATURAL ELEMENTS - Veronica, Desy; Chandra, Yulie Neila (Bambuti, 2020)
Mandarin is rich in vocabulary, including the form of æˆè¯chÃ©ngyÇ”, which is one of the most important parts in Mandarin. Every æˆè¯chÃ©ngyÇ” has its own background story, including history. Therefore, to understand the meaning of æˆè¯chÃ©ngyÇ” must understand the background of the story from æˆè¯chÃ©ngyÇ”. This article describes the idiomatic meaning of æˆè¯chÃ©ngyÇ” which has natural elements contained in the book of æˆè¯æ•…äº‹ChÃ©ngyÇ” GÃ¹shi. Each Han character (æ±‰å— HÃ nzÃ¬) that becomes an element inæˆè¯chÃ©ngyÇ” does not reflect the overall meaning of the forming element, so that in general theæˆè¯chÃ©ngyÇ” has idiomatic meaning. The method used in this writing is qualitative descriptive. There are 21æˆè¯chÃ©ngyÇ” with natural elements in the book of æˆè¯æ•…äº‹ ChÃ©ngyÇ” GÃ¹shi, however only one æˆè¯chÃ©ngyÇ” which contains partial idiom meanings, the other 20 of æˆè¯chÃ©ngyÇ” contains the full idiom meaning because of the forming elements do not reflect the idiomatic meaning. æˆè¯chÃ©ngyÇ” has a syntactic function in the sentence, as well as functions as advice, satire, and also praise to people indirectly.